Physico-chemical characteristics of nano-organo bentonite prepared using different organo-modifiers - A.M. Motawie; M.M. Madany; A.Z. El-Dakrory; H.M. Osman; E.A. Ismail; M.M. Badr; D.A. El-Komy; D.E. Abulyazied (Egyptian Journal of Petroleum)
Different types of nano-organo bentonite (NOB) were prepared from the Egyptian Bentonite (EB). EB was characterized by energy dispersive X-ray EDX. It was purified from different impurities using a conventional method via the treatment with HCl and distilled water. The modification of the clay was carried out using different types of organo-modifiers namely; hexadecyl trimethyl ammonium bromide (HTAB), 3-aminopropyltriethoxysilane (Silane), octadecylamine (ODA), and dodecylamine (DDA). The cation exchange capacity (CEC) was measured for pristine bentonite after and before modification. The NB was characterized by FTIR, XRD, TEM, and TGA techniques. The obtained results indicated that variation of the interlayer space gallery was effected by the type of the penetrator used.